Karapandzic flap and Bernard-Burrow-Webster flap for reconstruction of the lower lip - Brinca, A (2012)
Squamous cell carcinoma is the most common malignant neoplasm of the lips, and in about 90% of cases it is located on the lower lip due to higher cumulative exposure to ultraviolet radiation. The authors present two surgical techniques for reconstruction of large lower lip defects, resulting from surgical excision of tumors, exemplifying and comparing them with two clinical cases.